Separacija-individuacija skozi pogled psihoanalize in nevrobiologije - Glavač, Timotej (Psihološka obzorja (Ljubljana), 2023)
The process of separation-individuation begins in early childhood and plays an important role in adolescence and emerging adulthood. An unsuccessfully resolved process has been shown to have long-term adverse consequences in one’s psychosocial functioning, symptoms of depression, anxiety and psychiatric illness. The early conceptualizations of separation-individuation largely focused on the environmental factors that might lead to problems in a healthily resolved process. More recent studies from the fields of genetic and neuroscientific research have improved our understanding of the neurobiological foundations of separation-individuation. Research on animal models has shown, that separation anxiety, a fundamental emotion accompanying separation individuation can be found in all mammals, which suggests that the process might have evolutionary origins. Behavioral genetics research has shown that separation anxiety disorder has a significant rate of heritability. While research from the field of molecular genetics has identified specific genes that are related to increased rates of separation anxiety and separation anxiety disorder. The present paper presents studies that highlight the importance of considering both environmental and genetic factors in understanding the process of separation-individuation.
Keywords: genetics; genetika; neurobiology; nevrobiologija; psihosocialno delovanje; psychosocial functioning; separacija-individuacija; separacijska anksioznost; separation anxiety; separation-individuation